Binding Investigation of Some Important Metal Ions Copper (I), Nickel (II), and Aluminium (III) with Bovine Serum Albumin Using Valid Spectroscopic Techniques - Hassan A. Alhazmi; Md Shamsher Alam; Mohammed Albratty; Asim Najmi; Ahmed A. Abdulhaq; Rym Hassani; Waquar Ahsan; Abdulrahman N. Qramish (Journal of Chemistry)
Studies based on the interaction of metals with proteins resulted in the development of promising metal-based compounds with encouraging medicinal potential. This study was aimed to utilize FT-IR and UV-Vis spectroscopic techniques to analyze the interactions of biologically significant metal ions, such as Al3+, Ni+2, and Cu+, with bovine serum albumin (BSA). Different concentrations of metal ions were interacted with BSA, and the complexes were analyzed using the two techniques. The change in the BSA secondary structure components such as β-sheet, β-antiparallel, α-helix, β-turn, and random coil were analyzed using second derivative resolution enhancement. The FT-IR spectroscopy suggested a marked decrease in the C=O stretching (corresponding to amide I) and C=N stretching (corresponding to amide II) intensities. Interestingly, upon complexation, a marked reduction (22.58–29.03%) in the α-helical component was observed with a considerable increase in the random coil component. The intensity of the absorption peak of BSA obtained using UV was observed to increase consecutively as the concentration of Cu+, Al3+, and Ni2+ ions increased. The binding constants for the BSA-Cu+, BSA-Ni+2, and BSA-Al+3 complexes were calculated to be 3.46 × 104 M−1, 1.28 × 104 M−1, and 2.08 × 104 M−1, respectively. It was concluded that the binding interaction decreased in the order Cu+ > Al3+ > Ni2+. These findings were similar to our previous findings using affinity capillary electrophoresis (ACE). Therefore, it can be inferred that the FT-IR and UV techniques might be utilised effectively to assess the metal-protein interaction and can have wide application in routine analysis. These techniques have several advantages in being simple, easy-to-perform, rapid, and affordable over other high-end techniques.